The barrier to contraceptive use among multiparous women in Indonesia - Ratna Dwi Wulandari; Agung Dwi Laksono; Ratu Matahari (Wolters Kluwer Medknow Publications, 2021)
Background: The lack of perception related to the risk of pregnancy and contraceptive use's side effects is the main reason for not using contraceptives. Objective: This study aimed to analyze barriers to contraceptive use among multiparous women in Indonesia. Methods: This study employed the 2017 Indonesia Demographic and Health Survey. The analysis unit was multiparous women aged 15-49 years old, and the sample was 25,543 women. The contraceptive use was the dependent variable, while the independent variables analyzed were residence, age, education, employment, wealth, and insurance. The study used a binary logistic regression to determine the barriers. Results: Women in urban areas were 1.100 times more likely not to use contraceptives than women in rural areas. All categories of age group are more likely to use contraception than the 45-49 age group. Multiparous women who had low education had a higher possibility of not using contraceptives. Unemployed multiparous women were 1.008 times more likely not to use contraceptives than employed multiparous women. In terms of wealth status, women with all wealth status tended not to use contraceptives than the richest. Conclusions: Multiparous women in Indonesia had five barriers to not using contraceptives. These included living in urban, being at younger ages, having no education, being unemployed, and having low wealth status.